The effect of bioenergy therapies on blood pressure and anxiety levels: A systematic review - Agus Setiawan; Tuti Herawati (Holistik Jurnal Kesehatan, 2024)
Background: Hypertension cases globally reach 22% of the world's total population, and are estimated to continue to increase every year. The impact of hypertension can cause complications of other heart diseases. Management techniques that can be used to overcome this with complementary therapy are energy-based or bioenergy therapy. Although several studies have used energy therapy, there has been no systematic examination of the effect of energy therapy on changes in blood pressure and anxiety. Purpose: To identify the bioenergetics actions that most influence changes in blood pressure, pulse rate and anxiety. Method: Systematic review research using PRISMA, PICO flow diagram, and searching for English language articles published in 2013 -2023. The databases used are PubMed, Scopus, Science Direct, Taylor & Francis. This research uses tools for the data selection process to extraction and CASP instruments to evaluate articles. Results: All articles used a randomized controlled trial design. The number of samples used ranged from 42-150 people from Asian and American ethnicity. Three articles about healing touch and Reiki can lower systolic, diastolic blood pressure and anxiety. Meanwhile, in one of the articles, Reiki is able to reduce systolic and diastolic blood pressure. One article healing touch affects anxiety. Both healing touch and Reiki articles had no effect on reducing systolic, diastolic blood pressure or anxiety. All research has medium and high method quality and meets the quality assessment components. Of the seven articles studied, there were differences in the influence on changes in blood pressure and anxiety. Conclusion: Bioenergy therapy can reduce blood pressure and anxiety.   Keywords: Anxiety; Bioenergy; Blood pressure; Complementary Therapies; Hypertension.   Pendahuluan: Kasus hipertensi secara global sebesar 22% dari total populasi dunia, diperkirakan setiap tahunnya meningkat. Dampak dari hipertensi dapat menyebabkan komplikasi penyakit jantung lainnya. Teknik manajemen yang dapat digunakan dalam mengatasinya dengan terapi komplementer yaitu terapi berbasis energi atau bioenergi. Meskipun beberapa penelitian banyak menggunakan terapi energi, namun belum ditemukan sistematis yang meneliti terapi energi yang berpengaruh terhadap perubahan tekanan darah dan anxiety. Tujuan: Untuk mengidentifikasi tindakan bioenergi yang paling berpengaruh terhadap perubahan tekanan darah, nadi, dan anxiety. Metode: Penelitian sistematik review menggunakan diagram alur PRISMA, PICO, dan mencari artikel bahasa Inggris yang diterbitkan dari tahun 2013 -2023.  Database yang digunakan adalah PubMed, Scopus, Science Direct, Taylor & Francis. Penelitian menggunakan tool covidence untuk proses seleksi data sampai ekstraksi dan instrumen CASP dalam mengevaluasi artikel. Hasil: Semua artikel menggunakan desain randomized controlled trials, Jumlah sampel yang digunakan berkisaran 42--150 orang dari etnik Asia dan Amerika. Tiga artikel healing touch dan Reiki dapat menurunkan tekanan darah sistolik, diastolic, dan anxiety. Sedangkan satu artikel Reiki dapat menurunkan tekanan darah sistolik dan diastolik. Satu artikel healing touch memengaruhi anxiety. Dua artikel healing touch dan Reiki tidak memiliki pengaruh terhadap penurunan tekanan darah sistolik, diastolic, maupun anxiety. Seluruh penelitian memiliki kualitas metode sedang dan tinggi serta memenuhi komponen penilaian kualitas. Dari ketujuh artikel yang diteliti terdapat perbedaan pengaruh terhadap perubahan tekanan darah dan anxiety. Simpulan: Terapi energi bioenergi dapat memengaruhi penurunan tekanan darah dan anxiety.   Kata Kunci: Anxiety; Bioenergi; Hipertensi; Tekanan Darah; Terapi Komplementer.